Anthropometric and Functional Profile of Selected vs. Non-Selected 13-to-17-Year-Old Soccer Players - Nughes, Erik (Sports (Basel), 2020)
The purpose of this study was to compare anthropometric and functional profiles of 13-to-17-year-old soccer players according to their competitive level. Height, body mass, percentage of body fat, countermovement jump height, change of direction ability, 5- and 15-m sprint times, repeated sprint ability (RSA), intermittent recovery performance, and dribbling skills were collected in 115 young Italian soccer players. Players were divided into selected (i.e., competing at national level, n = 17 U15 and 47 U17) and non-selected (i.e., competing at regional level, n = 43 U15 and 8 U17) groups. U17 selected players were taller, quicker over 5 and 15 m, more agile, and had better RSA, prolonged intermittent recovery ability, and dribbling skills than their non-selected counterparts (d = 0.28–0.55, p < 0.05). In particular, selected players showed lower times on the first three and the last shuttle of the RSA test (d = 0.28–0.34, p < 0.05). No significant differences were observed in U15 players (p > 0.05). Discriminant analysis revealed that dribbling skills, 15-m sprint time, and height best discriminate U17 players by competitive level (p < 0.001). Anthropometric characteristics and functional abilities can discriminate across competitive standards between male U17 but not U15 soccer players. In particular, these findings suggest the importance of dribbling skills, 15-m sprint, and height in U17 players.